Analisis sudut panel solar cell terhadap daya output dan efisiensi yang dihasilkan - Anoi, Yano Hurung; Yani, Ahmad; W, Yunanri (Universitas Muhammadiyah Metro, 2019)
One of the natural potentials as a source of electrical energy is solar energy. The sun is the main energy source for most of the processes that occur on the surface of the earth. Solar radiation received by the earth's surface is a fundamental input for many aspects, mainly an important parameter in the application of solar cells as electricity generation. Sun cells are devices that can convert sunlight into electrical energy. In this study the data collection of solar cell panel data is collected which includes the solar radiation data, the voltage data generated and the electric current data generated at each variation of the tilt angle 0o, 8o, and 16o. This study aims to discover the effect of changes in the slope angle of solar cell panels on the efficiency of solar power generation systems. The study method used is an experimental development method which is carried out by using the tilt angle variation of the solar panel. The angle used by taking the tilt angle of the solar panel on the negative x-axis which aims to find the maximum tilt angle value. From the test results of 50 Watt Peak (WP) solar power plant installation, it can be concluded that the highest efficiency occurs at an angle of 16o and at 09:00 with a value of 46.076 %, then the second occurs at an angle of 8o and at 09:00 with a value of 45,052 %, then the lowest efficiency occurs at a slope angle of 0o and at 09:00 with a value of 43,986 %. Keywords: Angles, 50 WP panel, solar cell, power output, & efficiency.